Reinforcement learning based electricity price forecasting in Blockchain based smart grid environment - Moti, Md Mahraj Murshalin Al; Uddin, Rafsan Shartaj; Anik, Abdul Hai; Saleh, Tanzim Bin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.